2010
DOI: 10.3892/ijmm_00000398
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents the impairment of advanced glycosylation end products (AGE) on macrophage lipid homeostasis by suppressing the receptor for AGE via peroxisome proliferator-activated receptor γ activation

Abstract: Abstract. Advanced glycosylation end products (AGE) and its receptor (RAGE) axis is involved in the regulation of lipid homeostasis and is critical in the pathogenesis of diabetic atherosclerosis. We investigated the protective role of resveratrol against the AGE-induced impairment on macrophage lipid homeostasis. In THP-1-derived macrophages, RAGE was dose-dependently induced by AGE and played a key role in the AGE-induced cholesterol accumulation. Resveratrol markedly reduced RAGE expression via peroxisome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…Which is the role of RAGE in promoting fat accumulation? Previous studies demonstrated a link between increased RAGE expression and activation of pathways that can promote lipid accumulation in many cell types/tissues and suggested that therapies preventing RAGE activation are able to reduce these effects [21, 30, 33, 34, 42]. Results obtained in this study emphasized the potential association between RAGE, lipid accumulation, and genes involved in lipid metabolism in the heart; however, they did not prove a direct cause-effect relationship.…”
Section: Discussioncontrasting
confidence: 78%
“…Which is the role of RAGE in promoting fat accumulation? Previous studies demonstrated a link between increased RAGE expression and activation of pathways that can promote lipid accumulation in many cell types/tissues and suggested that therapies preventing RAGE activation are able to reduce these effects [21, 30, 33, 34, 42]. Results obtained in this study emphasized the potential association between RAGE, lipid accumulation, and genes involved in lipid metabolism in the heart; however, they did not prove a direct cause-effect relationship.…”
Section: Discussioncontrasting
confidence: 78%